Vybrané měnové nástroje České národní banky - Makovský, Zdeněk (Univerzita Pardubice, 2002)
This article deals with monetary instruments used by Czech National Bank. The first part explains funktion and role of national bank. The second part deals with problems of bank rate and the last part is given to solution of rate of exchange of CZK.
Keywords: Česká národní banka; měnové nástroje; kurzy; česká měna; diskontní sazba